Efficacy and safety of tadalafil in a pediatric population with pulmonary arterial hypertension: phase 3 randomized, double‐blind placebo‐controlled study. (1st June 2021) - Ivy, Dunbar; Bonnet, Damien; Berger, Rolf; Meyer, Gisela M.B.; Baygani, Simin; Li, Baohui
Abstract : This study evaluated the efficacy and safety of tadalafil in pediatric patients with pulmonary arterial hypertension. This phase‐3, international, randomized, multicenter (24 weeks double‐blind placebo‐controlled period; two‐year, open‐labeled extension period), add‐on (patient's current endothelin receptor antagonist therapy) study included pediatric patients aged <18 years with pulmonary arterial hypertension. Patients received tadalafil 20 mg or 40 mg based on their weight (heavy‐weight: ≥40 kg; middle‐weight: ≥25 to <40 kg) or placebo orally once daily for 24 weeks. Primary endpoint was change from baseline in six‐minute walk distance in patients aged ≥6 years at Week 24. Sample size was amended from 134 to ≥34 patients, due to serious recruitment challenges. Therefore, statistical significance testing was not performed between treatment groups. Results showed that patient demographics and baseline characteristics ( N = 35; tadalafil = 17; placebo = 18) were comparable between treatment groups; median age was 14.2 years (6.2–17.9 years) and majority (71.4%, n = 25) of patients were in the heavy‐weight cohort. Least square mean (standard error) changes from baseline in six‐minute walk distance at Week 24 was numerically greater with tadalafil versus placebo (60.48 (20.41) vs 36.60 (20.78) meters; placebo‐adjusted mean difference (standard deviation) 23.88 (29.11)). Safety of tadalafil treatment was as expected without any new safety concerns. During study Period 1, two patients (one in each group) discontinued due to investigator's reported clinical worsening, and no deaths were reported. In conclusion, the statistical significance testing was not performed between the treatment groups due to low sample size; however, the study results show positive trend in improvement in non‐invasive measurements, commonly utilized by clinicians to evaluate the disease status for children with pulmonary arterial hypertension. Safety of tadalafil treatment was as expected without any new safety signals.